The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.26603/ijspt20170840
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Hip Arthroscopy in an Active Duty Military Population Utilizing a Criterion-Based Early Weight Bearing Progression

Abstract: Introduction: Hip arthroscopy allows surgeons to address intra-articular pathology of the hip while avoiding more invasive open surgical dislocation. However the post-operative rehabilitation protocols have varied greatly in the literature, with many having prolonged periods of limited motion and weight bearing. Purpose: The purpose of this study was to describe a criterion-based early weight bearing protocol following hip arthroscopy and investigate functional outcomes in the subjects who were active duty mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Furthermore, Tijssen et al [ 20 ] had a mean follow-up of 26.8 months (range 7.5–45.3) for their patients. Shaw et al [ 21 ] had followed their patients for a 6-month post-operative period, while Bennell et al reported 24-week follow-up and Mansell et al [ 23 ] reported 24-month follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Tijssen et al [ 20 ] had a mean follow-up of 26.8 months (range 7.5–45.3) for their patients. Shaw et al [ 21 ] had followed their patients for a 6-month post-operative period, while Bennell et al reported 24-week follow-up and Mansell et al [ 23 ] reported 24-month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The following phases of rehabilitation were set to establish healthy healing of the tissue, reduce pain, restore gait, strength and endurance, regain cardiovascular fitness and proprioception (Saavedra et al [ 19 ] and Mansell et al [ 23 ]) and regain range of motion (ROM) and ability to RTS without pain among the phase-based studies [ 1 , 19–21 , 23 ]. Saavedra et al [ 19 ] and Shaw et al [ 21 ] did not include pre-operative phases. Finally, Shaw et al [ 21 ] designed their protocol to control pain, increase active ROM, normalize gait, restore strength and ability to perform daily living activities, increase agility movements and help patients to return to and pass the Army Physical Fitness Test (APFT).…”
Section: Resultsmentioning
confidence: 99%
“…Across all pooled data, four studies demonstrated extreme positive effects. Three of these studies [54, 101,120] involved participants undertaking high-level physical activity with elevated post-arthroscopy scores. Conversely, Michal et al [102] reported very low pre-arthroscopy scores in a cohort who underwent surgery for subspinal decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al recently reported on a series of 11 active-duty military patients who were allowed to fully weight bear as tolerated following hip arthroscopy for FAI. 24 Most of the patients in their cohort underwent osteoplasty and labral repair. They used specific criteria to allow crutch-wean, including a near-normal pain-free gait pattern.…”
Section: Postoperative Weight-bearingmentioning
confidence: 99%